Seismic Drift Control Criteria - Teal, Edward J. (Engineering Journal, 1975)
Because building drift coefficients have been locked in with building dynamic response to many different earthquake ground motions and many opinions about probable, credible, and possible ground motions, this very important index of building seismic performance has been difficult to evaluate and standardize. It is suggested that the known part of the drift problem, the building flexibility and weight, be separated out into a Dynamic Flexibility Index. In order to compare buildings of different heights in relation to their dynamic response, which also varies with height, a Seismic Drift Index is suggested. A number of representative buildings have been analyzed for these indexes. These buildings show some indication of the practical index limits and set the stage for standardizing flexibility evaluation and criteria. Continued use of standardized evaluation indexes should provide a clearer picture of the practical limits involved and a ready means of evaluating performance on an equal comparative basis.